Alterations in consumer behavior on food purchases during covid-19 pandemic - Oliveira, Márcio (2021)
The present research aims to assess the impact of the COVID-19 pandemic on the behavior of Portuguese consumers concerning the purchase of food. For this purpose, a quantitative study was performed, using a sample composed of 741 Portuguese consumers. The study was carried out between November 2020 and February 2021, a period during which the most severe measures of social isolation were imposed by the Portuguese government since the beginning of the pandemic in March 2020. The results show that during the pandemic, consumers changed their behavior patterns, specifically: in the frequency of shopping; the use of transport to carry out the purchases; the amount of the budget allocated for this purpose; and the channels used to purchase. Based on these results, managers and policy makers will be able to adjust or redefine their strategies to meet new consumer preferences, thus promoting individual well-being and business success. Our research is original as it is focused on the Portuguese context at a specific point in time motivated by the external factors that arose from the dissemination of the Covid-19 pandemic, consequently affecting consumers' behavior on food purchase. Furthermore, it adds value to the literature with new findings on consumer behavior change within a pandemic environment, and the application of practical assistance to market practitioners as well as advice to policy makers.